Mixed Thymoma in a Goat - Headley, Selwyn A.; Sukura, Antti (Brazilian Journal of Veterinary Pathology, 2011)
This article describes the gross, histopathological, and immunohistochemical findings of a mixed thymoma in a 2-year-old, mixed-breed, female goat. A large space-occupying neoplastic growth was observed within the cranial thoracic cavity, which by histology was well-encapsulated and formed by the proliferation of spindle-shaped epithelial cells arranged in solid sheets or rosette-like formations with varying accumulations of lymphocytes. Immunohistochemistry demonstrated that the neoplastic epithelial cells expressed cytokeratin, with negative immunoreactivity to vimentin, thyroglobulin, Chromogranin A, neuron-specific enolase, and glial fibrillary acidic protein. The lymphocytic population expressed CD3 and CD2. These findings favor a diagnosis of mixed thymoma.